PENGEMBANGAN SISTEM E-VOTING DENGAN PROTOKOL TWO CENTRAL FACILITIES MENGGUNAKAN FINGERPRINT SEBAGAI OTENTIKASI VOTER - Sikki, Muhammad Ilyas; Guritman, Sugi; Rahmawan, Hendra (Program Studi Teknik Elektro Fakultas Teknik Universitas Islam 45 Bekasi, 2013)
The e-voting system which developed using two central facilities protokol consist of three component that is voting machine as client for interaction with voter, central legitimization agency (CLA)  as server  voter authentication, and central tabulating facility (CTF) as server for result recapitulation voter vote count. Research in this thesis just focused to voter authentication process on voting machine toward database of voter that stored in CLA with using fingerprint biometric technology. Fingerprint biometric technology used for voter registration process, voter verification process, and voter authentication process who will doing election. Registration process for acquire voter fingerprint image database, verification process to be sure voter database can be verificated or not, and authentication process for voter authorization who can be permitted or not by system give of vote in election